Pedagogical trends in the contents of Lithuanian primers (the end of the 19th century to the beginning of the 20th century) - Simaška, K. (Psichologija, 1965)
This is about the Lithuanian nation's struggle for democratic schools, teaching in their native language created the conditions for the recovery of educational thought, which in turn gave a positive impetus to the renewal of primers. Several dichotomies existed between educator publicists (J. Adomaitis-Šernas, J. Šliūpas, P. Višinskis, et al.) and others opposed to church obscurantism; anti-human morality opposed to secular, experience-based morality; and the dogmatic training process understanding opposed to active and conscious learning. They proved that the scientific, perceptual-based instruction allows the formation of the correct approach to the world around them and has extensive educational value.Representatives of the petty bourgeoisie free education (A. Jakučionis, K. Skabeika, S. Matijošaitis, etc.), despite repeating the errors inherent in this approach, expressed democratic views on school tasks and debated about the clerical bourgeois education.A new approach to the tasks, content, and the learning process in elementary school also had an impact upon primers. Initial training in reading tasks are mixed up with initial world studies tasks in order to prepare students for further systematic training; it was used in a variety of languages and ways of thinking. This allowed for easy, fair, and deliberate reading to develop.Many of the primers had a positive educational value. They spread the word about a materialistic approach to life and irreligious morals, condemned czarist oppression, and in some cases social injustice, too.
Keywords: history of pedagogy; primers; Lithuanian language